A quadratic's general form is:
![ax^2+bx+c](https://img.qammunity.org/2023/formulas/mathematics/high-school/knmog89o03f8dx9fluvbqb64q9rt61y6kp.png)
Our trinomial given is:
![x^2-x+c](https://img.qammunity.org/2023/formulas/mathematics/college/eh73e23hzj5j2ortbyl6ikdej8slysxfar.png)
From matching it with the general form, we can say that:
![\begin{gathered} a=1 \\ b=-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/kcrui8yayu5um694zp46hnxbkvnhu53r02.png)
For this to be a perfect square trinomial, c will take the value:
![c=((b)/(2))^2^{}](https://img.qammunity.org/2023/formulas/mathematics/college/er26g5nzegdjbtmybcrnihl9v6ynsv9ord.png)
We know b = -1, thus c will be:
![\begin{gathered} c=((b)/(2))^2 \\ c=(-(1)/(2))^2 \\ c=(1)/(4) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/gqogdbo1mqcjc3sl6dzvkheyrzixjj5fcz.png)
Thus, the value of c that will make this a perfect square trinomial:
![c=(1)/(4)](https://img.qammunity.org/2023/formulas/mathematics/college/fpsi6raj81uyyg0brjmnbnz0e62nkswe43.png)